Contracting between Firms: Empirical Evidence - Iyer, Rajkamal; Sautner, Zacharias (The Review of Economics and Statistics, 2018)
We analyze contracts between a large buyer and her suppliers. We find that contracts with critical product suppliers contain more clauses that address moral hazard, primarily through monitoring. If holdup concerns are larger, there are more contractual protections against it. Over time, contracts with the same supplier include additional provisions that address moral hazard through monitoring. This dynamic effect is strongest for service contracts, where observability and verifiability are initially lower. Our findings indicate that contracts become more complete over time and provide support to incomplete-contracting models that argue that contracts become more complete as contracting costs decrease.